Heart protective effects of cardioactive drugs associated with antineoplastic treatment against breast cancer - Fonseca, Tatiana; Pessoa, Vinícius; Miranda, Dalmo; Martins, Daniela; Costa, Natália; Lima, Hayana (Contemporary Oncology/Współczesna Onkologia, 2022)
The prevalence of breast cancer in women is a fundamental problem in public health worldwide. There is consensual evidence that many chemotherapeutic agents might have harmful effects on the cardiovascular system of patients. The cardiotoxicity of chemotherapeutic drugs might lead to ventricular systolic dysfunction and heart failure, and consequently cardioactive drugs, such as antihypertensive, might mitigate those cardiac dysfunctions. Thus, this study carried out an integrative literature review on the potential benefits of cardioactive drugs in cardiovascular repercussions resulting from chemotherapy (CT), especially in women with breast cancer. The research involved articles available on the PubMed, LILACS, and MedLine databases, using as descriptors “breast cancer”, “chemotherapy”, “cardiotoxicity”, and “antihypertensive”; 11 articles were selected. The data corroborate an association between the use of antineoplastic drugs (anthracyclines, fluorouracil, and anti-HER2 monoclonal antibody, trastuzumab) and cardiotoxic effects, and anthracyclines are the most studied CT drugs in relation to cardiac dysfunction. The cardioprotective effect of cardioactive drugs, including non-selective and selective beta-blockers classes, angiotensin-converting enzyme inhibitors, and angiotensin receptor blockers, could be observed in clinical outcomes. Nonetheless, the drugs have different cardioprotective effects on breast cancer patients and left ventricular ejection fraction; the serum concentrations of troponins and brain natriuretic peptide were the most frequent parameters analysed in selected articles. In summary, cardiovascular parameters should be followed-up in patients undergoing oncology treatment in all stages, regardless of the therapeutic scheme carried out, given the risk of developing and worsening such heart conditions.